Commodity risk assessment of Tilia cordata and Tilia platyphyllos plants from the UK - EFSA Panel on Plant Health (PLH); Claude Bragard; Paula Baptista; Elisavet Chatzivassiliou; Francesco Di Serio; Josep Anton Jaques Miret; Annemarie Fejer Justesen; Alan MacLeod; Christer Sven Magnusson; Panagiotis Milonas; Juan A. Navas‐Cortes; Stephen Parnell; et al. (EFSA Journal)
Abstract The European Commission requested the EFSA Panel on Plant Health to prepare and deliver risk assessments for commodities listed in Commission Implementing Regulation (EU) 2018/2019 as ‘High risk plants, plant products and other objects’. This Scientific Opinion covers plant health risks posed by plants of Tilia cordata and T. platyphyllos imported from the United Kingdom (UK) as: (a) bundles of budwood/graftwood; (b) 1‐ to 2‐year‐old whips, seedlings or transplants; (c) bundles of 1‐ to 2‐year‐old cell grown plants; (d) 1‐ to 7‐year‐old bare root single plants; and (e) up to 25‐year‐old single plants in pots, taking into account the available scientific information provided by the UK. A list of pests potentially associated with the commodities was compiled. The relevance of any pest was assessed based on evidence following defined criteria. None of the pests on the list fulfilled all relevant criteria and therefore none were selected for further evaluation. As a result, risk mitigation measures proposed in the technical dossier from the UK were listed, but not further evaluated.